Peran Ruang Terbuka Hijau sebagai Nature Based Solution dalam Mendukung Strategi Dekarbonisasi dan Keberlanjutan Organisasi - Aisha Putri Khoirunisa; Ardi Santoso; Bernard Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of Green Open Space (GOS) as Nature-Based Solutions (NbS) in supporting organizational decarbonization strategies and sustainability. The method used is a Systematic Literature Review (SLR) with a qualitative approach, involving the examination of various scientific journals, international organizational reports, and relevant regulations covering the period 2016–2025. This review was conducted to obtain a more comprehensive understanding of the contribution of GOS in emission reduction and the strengthening of sustainability practices. The findings show that GOS contributes to carbon sequestration, improved air quality, microclimate regulation, rainwater management, and biodiversity conservation within organizational environments. The carbon absorption capacity of GOS is recorded at 140,920 tons of CO₂ per year, or approximately 20.65% of the organization’s total fuel emissions of 682,338 tons of CO₂ per year. Although it is not yet able to offset all organizational emissions, GOS plays a strategic role as a supporting instrument for decarbonization and the implementation of Environmental, Social, and Governance (ESG) principles. Therefore, GOS management needs to be integrated with energy efficiency strategies and organizational sustainability efforts to ensure that both ecological and operational benefits can be optimally achieved.